2019
DOI: 10.1371/journal.pone.0219937
|View full text |Cite
|
Sign up to set email alerts
|

What factors are associated with the poor prognosis of anal adenocarcinoma compared with low-lying rectal adenocarcinoma based on a population analysis: A propensity score matching study

Abstract: Purpose Anal adenocarcinoma (AA) represents a rare condition, and little is known about the predictive factors of the outcomes or the optimal TNM staging system for curable AA. Using population-based data, we preliminarily sought to determine the prognostic factors and evaluate the existing T and N staging criteria of AA. Methods We analyzed the Surveillance, Epidemiology, and End Results 18 database to identify patients 20–80 years old who were diagnosed with AA or rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Low survival outcomes are also observed in the Franklin et al and Lewis et al studies [ 10 , 15 ]. More recent studies are also in agreement, such as the one by Wang et al in 2019 that has shown adenocarcinoma of the anus having a worse prognosis than rectal adenocarcinoma and, in addition, stating that the T staging criteria for anal carcinoma may not be valid for staging anal adenocarcinoma [ 14 ].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Low survival outcomes are also observed in the Franklin et al and Lewis et al studies [ 10 , 15 ]. More recent studies are also in agreement, such as the one by Wang et al in 2019 that has shown adenocarcinoma of the anus having a worse prognosis than rectal adenocarcinoma and, in addition, stating that the T staging criteria for anal carcinoma may not be valid for staging anal adenocarcinoma [ 14 ].…”
Section: Discussionmentioning
confidence: 76%
“…The studies by Bertelson et al [ 9 ], Franklin et al [ 10 ], Lewis et al [ 15 ], Wang et al [ 14 ], McKenna et al [ 12 ], Leong et al [ 13 ] and Gogna et al [ 20 ] did not provide values for the 5-year overall survival rates or any OS rate values for each treatment group. In the Franklin et al study of 307 patients, the 1-, 3-, 5- and 10-year survival rates were 76.8%, 46.2%, 30.2% and 16.2%, respectively.…”
Section: Resultsmentioning
confidence: 99%